1987
DOI: 10.1056/nejm198711053171902
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Administration to Treat Possible Occult Bacteremia in Febrile Children

Abstract: We performed a prospective, randomized, placebo-controlled, double-blind clinical trial of antibiotic administration to treat possible occult bacteremia in febrile children. A total of 955 children aged 3 to 36 months with temperatures greater than or equal to 39.0 degrees C and no focal bacterial infection were enrolled at the emergency departments of two children's hospitals from January 1982 until July 1984. Blood samples for culture were obtained, and the children were randomly assigned to receive either o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
4

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(68 citation statements)
references
References 21 publications
3
61
0
4
Order By: Relevance
“…In 1987, Jaffe et al [13] evaluated children between the ages of 3 and 36 months and discovered a 2.87% rate of bacteremia and an important presence of type-b H. influenzae. In 1993, Bass et al also evaluated children between 3 and 36 months and discovered occult bacteremia in 11.5% of the patients, with 10% having infection by type-b H. influenzae [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 1987, Jaffe et al [13] evaluated children between the ages of 3 and 36 months and discovered a 2.87% rate of bacteremia and an important presence of type-b H. influenzae. In 1993, Bass et al also evaluated children between 3 and 36 months and discovered occult bacteremia in 11.5% of the patients, with 10% having infection by type-b H. influenzae [14].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to diagnostic uncertainty and resultant concern about missing an evolving or occult invasive bacterial infection. 16,17 There is often no way to definitively differentiate a bacterial from a viral infection. Diagnostics aids such as rapid streptococcal antigen testing for pharyngitis 26 or clinical criteria for the diagnosis of occult bacteremia 27 are underused, and physicians rely on clinical judgment, which may be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Parental pressure for an antibiotic was selected because it is one of the most frequently cited factors by physicians in antibiotic overuse in children. 7,9,[20][21][22] …”
Section: Variable Selectionmentioning
confidence: 99%
“…Therefore, the reported rate of SBI was 0.08% (95% CI, 0.03%-0.17%; 6/7485). [9][10][11][12] Although the total number of patients who developed SBI was 8, 2 were from the no treatment group. 12 In a meta-analysis, Bulloch and colleagues 14 reported that the use of either oral antibiotics or intramuscular ceftriaxone did trend toward a reduced risk of serious infection; however, neither reached statistical significance (odds ratio [OR], 0.60; 95% CI, 0.10-3.49; and OR, 0.38; 95% CI, 0.12-1.17, respectively).…”
Section: Commentmentioning
confidence: 99%